2016
DOI: 10.1086/684194
|View full text |Cite
|
Sign up to set email alerts
|

New Ginkgophytes from the Upper Triassic–Lower Cretaceous of Spitsbergen and Edgeøya (Svalbard, Arctic Norway): The History of Ginkgoales on Svalbard

Abstract: Editor: Patrick S. Herendeen Premise of research. During the ongoing investigation of Upper Triassic-Lower Cretaceous plant macrofossils from Svalbard, Norway, some ginkgoalean leaf fossils were found from Carnian and Aptian deposits of Spitsbergen and Edgeøya that represent new ginkgophyte species. One new species is described as Baiera aquilonia sp. nov., and one ginkgophyte leaf is assigned to Ginkgoites sp. Along with the description of the new material, an overview of the presence and distribution of gink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…R e m a r k s. There is no clear consensus as to whether such foliage is placed in Ginkgo or Ginkgoites. Current opinions and views were outlined in Pott et al (2016); we follow that approach and place the specimen in Ginkgoites but with close resemblance to what is commonly described as Ginkgo(ites) huttonii. The specimen is very similar in shape, number of veins and measurements to specimens that Heer (1876a) and Vachrameev and Doludenko (1961) described as Ginkgo(ites) huttonii from the Irkutsk and Bureya basins in Siberia.…”
Section: Ginkgoites Sewardmentioning
confidence: 99%
“…R e m a r k s. There is no clear consensus as to whether such foliage is placed in Ginkgo or Ginkgoites. Current opinions and views were outlined in Pott et al (2016); we follow that approach and place the specimen in Ginkgoites but with close resemblance to what is commonly described as Ginkgo(ites) huttonii. The specimen is very similar in shape, number of veins and measurements to specimens that Heer (1876a) and Vachrameev and Doludenko (1961) described as Ginkgo(ites) huttonii from the Irkutsk and Bureya basins in Siberia.…”
Section: Ginkgoites Sewardmentioning
confidence: 99%
“…Based on the observed stratigraphic sequences and sedimentary structures -as ''herring-bone'' lamination and typical rhythmites with cross-lamination containing mud drapes and re-activation surfaces -, the sedimentary interpretation relates these deposits with highly tidally-influenced fluvial environments close to the sea, departing from deposits containing the other mentioned Ginkgoalean leaves that show depositional conditions with a minor tidal influence (Querol et al, 1992;Villanueva-Amadoz et al, 2010;Sender, 2012). Until the beginning of the 21th century, the evidence showed that both genera Ginkgoites and Sphenobaiera had disappeared from western Eurasia during the Early Cretaceous, being restricted to the Siberian-Canadian province since the late Aptian or early Albian (Vakhrameyeev, 1991;Pott et al, 2016). Nevertheless, evidences confirming the presence of these ginkgoalean genera have been detected in middle-upper Albian deposits of the Iberian Plate, within the southwestern part of the EuroSinian province (Sender et al, 2008;this study).…”
Section: Palaeoenvironmental and Palaeophytogeographical Implicationsmentioning
confidence: 91%
“…On the basis of the morphology and dimensions of leaves, the arrangement of stomata in bands, the presence of cuticular ridges on the main epidermal cells, and the absence of papillae on the subsidiary cells in most stomata, P. doludenkoae is similar to P. grojecensis Reymanówna from the Lower Jurassic of Poland (Reymanówna, 1963), P. krassilovii Bugdaeva from the Lower Cretaceous of Southern Primorye (Bugdaeva and Markevich, 2009), and P. retusa Bose et Manum from the Lower Cretaceous of Spitsbergen (Bose and Manum, 1990;Pott et al, 2016). P. grojecensis differs from P. doludenkoae in a peculiar structure of the upper epidermis consisting of "units" of tetragonal cells of the same length, oriented either along or across the leaf axis.…”
Section: Taxonomic Description Of Pseudotorellia Speciesmentioning
confidence: 94%